A new multi‐scale model based on CFD and macroscopic calculation for corrugated structured packing column. Issue 8 (16th March 2013) - Sun, B.; He, L.; Liu, B.T.; Gu, F.; Liu, C.J.
Abstract : A multi‐scale approach with the combination of computational fluid dynamic (CFD) and macroscopic calculation methods has been proposed to predict the hydrodynamics behavior in the corrugated structured packing column. On the basis of the concept of the representative unit, the three‐dimensional (3‐D) volume of fluid (VOF) model of the structured packing is applied in the small scale simulation, and the stream split fraction coefficients and effective wetted area ratio are calculated. The unit network model, which is a mechanistic model, is applied in large scale calculation basing on the small scale results. The liquid holdup distribution in the entire column can be available by this multi‐scale method. A comparison between the simulation results and the experimental data of our previous work is given to validate the present model. The multi‐scale model is proved to be prospective to assist the analysis and design of structure packing columns in chemical engineering. © 2013 American Institute of Chemical Engineers AIChE J, 59: 3119–3130, 2013